The effect of a situation model nursing education action program on gender-bias awareness and gender-friendliness barriers in novice nursing students. (July 2021) - Pai, Hsiang-Chu; Wu, Pei-Ling; Hsu, Wen-Yi; Hung, Chao-An; Liu, Nai-Yu; Yen, Wen-Jiuan
Abstract: Aim: This study presents a workshop on the Situation Model Nursing Education Action program, examines how to promote gender awareness and decrease barriers related to differences in gender friendliness through the implementation of this program and tracks the trends of the relevant variables. Design: Pre- and post-observations and a cohort study were conducted. Methods: A total of 58 nursing students (42 females and 16 males) were included. Nursing students were offered a gender-care intervention as two 90-minute workshops and surveys that measure gender awareness and gender friendliness were administered. Results: The results concerned gender-bias awareness and gender-friendliness barriers scores across the four weeks of the program intervention, with the generalized estimated difference score compared with the Week 1 baseline. Mean student scores showed that gender-bias awareness was significantly decreased at Week 2 ( p < .001) and Week 4 ( p < .001) and that mean gender-friendliness barrier scores significantly declined at Week 4 ( p < .001). Conclusions: The findings indicate that a faculty professional learning community workshop that facilitates intentional behavioral change can help faculty to become aware of gender bias, which can improve students' gender awareness through clinical case discussion and lead to a decline in barriers to students' gender friendliness. Highlights: Nursing education should attempt to improve students' gender awareness. A faculty community workshop that helps faculty to become aware of gender bias. The Situation Model Nursing Education Action Program was developed by the faculty community team. A Situation Model Nursing Education Action Program was shown to improve students' gender-bias awareness.